Pelaksanaan Prinsip 5C dalam Penyaluran Dana Pembiayaan Murabahah - Putra, Muhahammad Deni; Ningsih, Weli Widia (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2023)
The purpose of this study was to find out how murabahah financing is at BMT Amanah Umat Taram Payakumbuh. The type of research that the authors use is field research. Data collection techniques use interviews, and documentation. Data processing was carried out in a qualitative descriptive manner, through a process of data reduction, data presentation, and drawing conclusions. Based on the results of the research we found first, character in assessing the customer character of the BMT performs by first assessing directly how the character of the customer itself is at the beginning of applying for financing and as a support it is also seen from the neighborhood around the prospective customer. Second, capital, in this case, BMT looks at all income received by prospective customers, both routine and incentives and other additional income. third, the capacity of BMT in checking the ability to pay prospective BMT customers by looking at how many payments are received and expenses that must be financed each month, then BMT looks at the remaining capital of the customer earlier whether it is enough to pay for the proposed financing estimate. fourth, collateral for prospective customers who wish to apply for financing of > IDR 10,000,000, the collateral that must be provided by the prospective customer is in the form of a certificate. Meanwhile, for prospective customers who wish to apply for financing of < IDR 1,000,000, the loan provided by the prospective customer can be in the form of household appliances such as televisions, washing machines, and refrigerators. Fifth, condition of economy In this case the BMT assesses the economic condition of the prospective customer from the development of the business being carried out whether it is progressing or experiencing setbacks in its efforts.